Repositioning Chromones for Early Anti-inflammatory Treatment of COVID-19 - Sestili, Piero; Stocchi, Vilberto (Frontiers in Pharmacology, 2020)
COVID-19 pandemic is posing an unprecedented sanitary threat. In the absence of specific vaccines and anti-SARS-CoV-2 drugs, medicines that may assist to tackle the emergency and limit the high number of fatalities are urgently needed. Repositioning of available drugs to treat COVID-19 is the only and rapid option to the lack of direct antiviral agents and vaccines. In this light it is important to focus on available drugs which - based on their pharmacodynamics - could plausibly attenuate viral growth as well as COVID-19 worst complications. This is the case of chloroquine and tocilizumab which seem to limit virus replication and the severity of interstitial pneumonia, respectively. However these treatments, particularly those aimed at containing inflammation, are still reserved to the most severe cases. This commentary elaborates on the pharmacological rationale of repositioning the mast cell stabilizers cromones as adjunctive treatment for SARS‐CoV‐2 infections, and proposes their practical clinical testing as an early, safe and cost-effective anti-inflammatory intervention in COVID-19 to limit the eventual, secondary progression toward respiratory, life-threatening complications.